2020
DOI: 10.1016/j.jsams.2019.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Perceived exertion responses to wheelchair propulsion differ between novice able-bodied and trained wheelchair sportspeople

Abstract: Objectives: To investigate peripheral (RPEP) and central (RPEC) rating of perceived exertion during wheelchair propulsion in untrained able-bodied (AB) participants, and trained wheelchair rugby athletes with and without cervical spinal cord injury (CSCI).Design: Cross-sectional study.Methods: 38 participants (AB: n = 20; wheelchair rugby athletes with CSCI: n = 9; without CSCI: n = 9) completed an incremental wheelchair propulsion test to exhaustion on a motorised treadmill. Gas exchange measures and heart ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 26 publications
2
9
0
Order By: Relevance
“…The current study showed higher RPE p than RPE c scores: 9 ± 1 vs 7 ± 1. This concords with previous research in untrained able-bodied participants performing arm-crank [ 34 ], hand-cycle [ 35 ] and wheelchair propulsion [ 36 39 ]. Different results were observed when compared to elite wheelchair rugby athletes, where no differences between RPE p and RPE c after a GXT were identified [ 39 ].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The current study showed higher RPE p than RPE c scores: 9 ± 1 vs 7 ± 1. This concords with previous research in untrained able-bodied participants performing arm-crank [ 34 ], hand-cycle [ 35 ] and wheelchair propulsion [ 36 39 ]. Different results were observed when compared to elite wheelchair rugby athletes, where no differences between RPE p and RPE c after a GXT were identified [ 39 ].…”
Section: Discussionsupporting
confidence: 85%
“…This concords with previous research in untrained able-bodied participants performing arm-crank [34], hand-cycle [35] and wheelchair propulsion [36][37][38][39]. Different results were observed when compared to elite wheelchair rugby athletes, where no differences between RPE p and RPE c after a GXT were identified [39]. Wheelchair propulsion is a rather specific (and straining) movement [40], and because able-bodied participants are not used to this movement they mainly gave up because of local, not cardiorespiratory fatigue.…”
Section: Settings Of the Wheelchair-specific Aerobic Exercise Testsupporting
confidence: 85%
“…For discontinuous tests, the typical interval between stages was 45–60 s. Submaximal tests continued until [BLa] exceeded 4 mmol L −1 or RPE was rated as 17. The RPE criteria was used in TETRA where there may have been blunted lactate responses [ 12 ].…”
Section: Methodsmentioning
confidence: 99%
“…During the PPO test, participants were outfitted with a heart rate monitor (Polar, Kempele, Finland) and instructed to maintain a cranking frequency of 55–65 revolutions per minute (rpm) until exhaustion, or for a maximum duration of 30 min. After a 5-min warmup at a self-selected resistance and cadence, the load was increased by 10 Watts (W)/min (paraplegia) or 2 W/min (tetraplegia) starting at 0 W. Ratings of perceived exertion (RPE) were taken during the last 10 s of each minute of exercise using the 6–20 Borg Scale ( 20 ), using the adapted script for persons with SCI ( 21 ). The test was complete when participants experienced volitional exhaustion or after 30 min ( 22 ).…”
Section: Methodsmentioning
confidence: 99%